An investigation of sintering in electro exploded platinum nanopowder - Tan, Eugene Yixian. (2013)
From literature, bulk platinum in the microscale (between 0.5 to 2 micrometers) [21] is known to exhibit sintering at 1000 degrees C or higher [22]. However, when reducing platinum metal to the nanoscale, the characteristics of platinum may exhibit changes in its physical properties. The purpose of this research was to investigate if sintering can occur at much lower temperatures when platinum metal was reduced to the nanoscale, in the form of wire exploded platinum nanopowder.